Empregabilidade de profissionais em transição de carreira - Boucinha, Daniela (2017)
The present study sought to explore the topic of employability and its applications in the labor market. For this, two studies were developed: a quantitative empirical study and a theoretical essay. The first study aimed to identify the related variables and the predictors of employability in professionals who sought a career consulting service at one private University in Rio Grande do Sul. Correlations analyzes, comparisons between groups and hierarchical regression analyzes were performed. The findings indicate the career decision had significant and positive correlations with general adaptability and that Insight, Control, Confidence and Career Decision were significant predictors of Employability. The second study sought to explain the decline of traditional careers and the emergence of the demand for employability, pointing to the need for attention to workability and to the development of new skills for the contemporary job market.